Structural reorganization of SHP2 by oncogenic mutations and implications for oncoprotein resistance to allosteric inhibition. Issue 1 (December 2018) - LaRochelle, Jonathan; Fodor, Michelle; Vemulapalli, Vidyasiri; Mohseni, Morvarid; Wang, Ping; Stams, Travis; LaMarche, Matthew; Chopra, Rajiv; Acker, Michael; Blacklow, Stephen
Abstract Activating mutations inPTPN11, encoding the cytosolic protein tyrosine phosphatase SHP2, result in developmental disorders and act as oncogenic drivers in patients with hematologic cancers. The allosteric inhibitor SHP099 stabilizes the wild-type SHP2 enzyme in an autoinhibited conformation that is itself destabilized by oncogenic mutations. Here, we report the impact of the highly activated and most frequently observed mutation, E76K, on the structure of SHP2, and investigate the effect of E76K and other oncogenic mutations on allosteric inhibition by SHP099. SHP2E76K adopts an open conformation but can be restored to the closed, autoinhibited conformation, near-identical to the unoccupied wild-type enzyme, when complexed with SHP099. SHP099 inhibitory activity against oncogenic SHP2 variants in vitro and in cells scales inversely with the activating strength of the mutation, indicating that either oncoselective or vastly more potent inhibitors will be necessary to suppress oncogenic signaling by the most strongly activating SHP2 mutations in cancer. Activating mutations of the non-receptor protein tyrosine phosphatase SHP2 can cause cancer. Here the authors present the crystal structure of SHP2E76K, the most frequent cancer-associated SHP2 mutation, which adopts an open-state structure and show that the allosteric inhibitor SHP099 can revert SHP2E76K to its closed, autoinhibited conformation.